PENGARUH MODAL PSIKOLOGIS TERHADAP ACADEMIC ENGAGEMENT (STUDI PADA MAHASISWA UNIVERSITAS X) - Yohanes Crisostomus; Kiky D.H. Saraswati (Provitae: Jurnal Psikologi Pendidikan, 2023)
Education is a very important thing at this time. During their education, of course, students are expected to have adequate knowledge and abilities as measured by their academic achievements. In many previous studies, it was concluded that academic achievement is influenced by various factors, one of which is academic engagement. There are several personal factors that can affect academic engagement, such as self-efficacy, hope, and optimism. These factors are part of psychological capital. Based on these references, this study was conducted to determine the impact of psychological capital on academic engagement among students of University X. This research is a quantitative study. Data collection is carried out by distributing questionnaires. The questionnaires used were the Psychological Capital Questionnaire and the Utrecht Work Engagement Scale-Student. A total of 312 participants with an age range of 18 years to 24 years were involved in this study. Based on the results of the regression analysis between psychological capital and academic engagement, the results obtained are F (1.310) = 86.997, p = 0.000, and R2 = 0.219. This shows that there is a significant impact of psychological capital while the contribution is 21.9% on the academic engagement of the students of University X.